(untitled) (Scientific journal of the Fergana State University, 2025)
This article focuses on the study of the cultural and linguistic characteristics of lexical units related to superstitions in German and Uzbek languages. Superstitions have been an integral part of the culture and lives of people over centuries. The study analyzes the history, classification, and educational significance of this genre. Superstitions, as a genre of oral folklore, are found among all peoples of the world, but scientific research in this area is still insufficient. The linguistic and cultural features of superstitions in German and Uzbek languages are studied using a comparative method. Folklore works, religious myths, and dictionaries were used as sources. The conclusion highlights the educational significance of the superstition genre and its critical role in the lives of people.